A systematic pan-cancer analysis of PXDN as a potential target for clinical diagnosis and treatment - Zhou, Xiaohu; Sun, Qiang; Xu, Chang; Zhou, Zheng; Chen, Xiaoquan; Zhu, Xiuping; Huang, Zhaoshuai; Wang, Weilin; Shi, Yanjun (Frontiers in Oncology, 2022)
Peroxidasin (PXDN), also known as vascular peroxidase-1, is a newly discovered heme-containing peroxidase; it is involved in the formation of extracellular mesenchyme, and it catalyzes various substrate oxidation reactions in humans. However, the role and specific mechanism of PXDN in tumor are unclear, and no systematic pan-cancer studies on PXDN have been reported to date. This study employed data from multiple databases, including The Cancer Genome Atlas and The Genotype-Tissue Expression, to conduct a specific pan-cancer analysis of the effects of PXDN expression on cancer prognosis. Further, we evaluated the association of PXDN expression with DNA methylation status, tumor mutation burden, and microsatellite instability. Additionally, for the first time, the relationship of PXDN with the tumor microenvironment and infiltration of fibroblasts and different immune cells within different tumors was explored, and the underlying molecular mechanism was determined. Our results provide a comprehensive understanding of the carcinogenicity of PXDN in different tumors and suggest that PXDN may be a potential target for tumor immunotherapy, providing a new direction for improving clinical diagnosis and treatment.